Predicting dengue incidence using panel data analysis - Mela Firdaust; Ririh Yudhastuti; Mahmudah Mahmudah; Hari B. Notobroto (AOSIS, 2023)
Dengue is the most rapidly spreading infectious disease, especially in Indonesia. Dengue virus is transmitted by the bite of female Aedes mosquitoes. The high human population density and proximity to vector breeding places strengthen the interaction between the virus, vector, and humans as hosts. Using dengue incidence panel data during 2018-2019 in 34 provinces in Indonesia, this study examined the effect of human population density as a demographic variable and vector control on dengue incidence in Indonesia. The time series data were analyzed using EViews. The fixed effect model estimation showed that dengue incidence was significantly associated with demographic variables measured as human population density, with a P-value of 0.02. The vector control variable shows an insignificant association with dengue incidence. But simultaneous analysis between human population density and vector control on dengue incidence has a significant association with probability F (statistic) = 0.000. Our study demonstrated that densely populated provinces in Indonesia have a very high incidence of dengue. Improving sanitation in densely populated settlements can prevent and control dengue incidence.